High-Resolution Reconstruction of Dissolved Oxygen Levels in the Baltic Sea With Bivalves – a Multi-Species Comparison (Arctica islandica, Astarte borealis, Astarte elliptica) - Schöne, Bernd R.; Huang, Xizhi; Jantschke, Anne; Mertz-Kraus, Regina; Zettler, Michael L. (Frontiers in Marine Science, 2022)
An increasing area of shallow-marine benthic habitats, specifically in the Baltic Sea, is affected by seasonal oxygen depletion. To place the current spread of oxygen deficiency into context and quantify the contribution of anthropogenic ecosystem perturbation to this development, high-resolution archives for the pre-instrumental era are needed. As recently demonstrated, shells of the bivalve mollusk, Arctica islandica fulfil this task with molar Mn/Cashell ratios as proxies for dissolved oxygen (DO) levels in the water column. Since the ocean quahog is inhomogeneously distributed in the Baltic Sea and may not be present in museum collections or found throughout sedimentary sequences, the present study evaluated whether two other common bivalves, Astarte elliptica and Astarte borealis can be used interchangeably or alternatively as proxy DO recorders. Once mathematically resampled and corrected for shell growth rate-related kinetic effects and (some) vital effects, Mn/Cashell data of all three species (age ten onward in A. islandica) were statistically significantly (p < 0.0001) linearly and inversely correlated to DO concentration in the free water column above seafloor (r = –0.66 to –0.75, corresponding to 43 to 56% explained variability). A. elliptica may provide slightly more precise DO data (1σ error of ±1.5 mL/L) than A. islandica or A. borealis ( ± 1.6 mL/L), but has a shorter lifespan. Both Astarte species show a stronger correlation with DO than A. islandica, because their biomineralization seems to be less severely hampered by oxygen and salinity stress. In turn, A. islandica grows faster resulting in less time-averaged data. During youth, the ocean quahog typically incorporates a disproportionately large amount of manganese into its shell, possibly because food intake occurs directly at the sediment-water interface where Mn-rich porewater diffuses out of the sediment. With increasing age, however, A. islandica seems to generate a gradually stronger inhaling water current and takes in a larger proportion of water farther away from the fluffy layer. As demonstrated here, all three studied species can be used as DO archives, though species-specific limitations should be kept in mind.